Effects of integrated blood purification on haemodynamics and oxygen metabolism in children with severe sepsis - Ma, Hekai; Wang, Zhiyuan; Geng, Jiahao; Zhao, Junlin; Wang, Tuanjie; Liu, Ling; Xu, Yuping; Liu, Weiqing; Wang, Min; Zhao, Lan; Li, Shujun (Frontiers in Medicine, 2024)
Objective: To investigate the effects of integrated blood purification on haemodynamics and oxygen metabolism in children with severe sepsis. Methods: Clinical data of 12 children with severe sepsis admitted to the paediatric intensive care unit of our hospital between October 2021 and June 2022 were retrospectively analysed. All patients were treated with integrated blood purification, and changes in haemodynamic parameters, including heart rate, blood pressure, mean arterial pressure and cardiac output, and oxygen metabolism parameters (blood lactic acid, oxygen delivery, oxygen consumption and oxygen extraction rate) were observed before and after treatment. Results: The heart rate (134[106,160] vs 111[101,128], p=0.037), central venous pressure (9[7,10] vs 8[7,9], p=0.04), stroke output (28[18,43] vs 21[15,31], p=0.01), blood lactate (3.3[2,4] vs 2.5[1.3,3.6], p=0.015), oxygen consumption (165.99[121.44,230.31] vs 124.18[82.51,162.86], p=0.041) and oxygen extraction rate (38.83[31.87,44.62] vs 28.67[21.05,32.72], p=0.019) were decreased, whereas systolic blood pressure (97[83,104] vs 107[94,116], p=0.033) and central venous oxygen pressure (32[29, 37] vs 39[34,46], p=0.005) were increased in the children after treatment compared with before treatment. There were no statistically significant differences in diastolic blood pressure, mean arterial pressure, cardiac output, arterial oxygen pressure and oxygen delivery before and after treatment (all p>0.05). Conclusion: Integrated blood purification can improve haemodynamic and oxygen metabolism parameters in children with severe sepsis, with a high value in clinical application.